Rural development drives temporal turnover in plant diversity in a China’s scenic area - Jia Zhang; Weicheng Li; Guofu Yang; Yue Wang; Xinxin Ji; Xiaojian Zhang; Yijun Lu (Environmental Research Communications)
Rural development has the potential to improve the well-being of villagers, but it may also impact local plant diversity. In addition, plant diversity differs across various subareas of rural development efforts in scenic areas, reflecting variations along the center-periphery gradient. To explore the relationship between economic development, plant diversity, and villagers’ well-being in villages within scenic areas during the rural development process, this study analyzed plant species data and satellite remote sensing images between 1984 and 2021, focusing on changes in land-use types in the Hangzhou West Lake Scenic Area and their impacts on plant diversity in the central, middle, and peripheral scenic areas. The results indicated that the area of rural construction land decreased, compared to 1984, while other land use types showed varying degrees of increase. Specifically, part of the forest in the peripheral scenic area was transformed into tea fields, resulting in an observable increase in the overall area of tea field. Moreover, the number of plant species decreased along the center-periphery gradient of the scenic spot. The greatest differences in the number of plant species and increases in the number of invasive plants were found in the peripheral scenic area, reflecting the greater impact of rural development in this region. Additionally, the number of rare and endangered plant species increased the most in the central scenic area in recent years, which was related to the use of urban green space to protect such plants. Ellenberg’s ecological indicator values (EIVs) indicated an increase in the number of species preferring shady locations and acidic soils in the scenic areas. The changes in land use and production and business activity strategies in the villages of the West Lake Scenic Area improved the villagers’ well-being, and the resulting factors such as the introduction of non-indigenous plants and environmental filtering changed local plant diversity. Therefore, the administrators should carefully consider the trade-off between conserving biodiversity and enhancing the well-being of the local villagers. The findings offer evidence of how different economic development models over time can influence rural biodiversity and villagers’ well-being, providing a reference for sustainable development in scenic spot villages.